Effect of equipment dead space on multiple breath washout measures. Issue 3 (21st January 2015) - Benseler, Anouk; Stanojevic, Sanja; Jensen, Renee; Gustafsson, Per; Ratjen, Felix
Abstract Background and objective Multiple breath inert gas washout (MBW) systems are designed to minimize equipment dead space volume (Vd). Animal and infant studies have demonstrated the impact of increased Vd on MBW measurements. In this study, we investigate the effect of Vd of a nitrogen (N2) MBW system on MBW measurements in preschool children. Methods N2 MBW measurements were performed in healthy adults under standard conditions; Vd was added to match the relationship between Vd and lung volumes observed in preschool children. Subsequently, subjects were measured on a sulfur hexafluoride (SF6) MBW system under standard conditions and with Vd added to match that of the N2 MBW system. Healthy preschool children and children with cystic fibrosis were tested on both the N2 MBW and SF6 MBW in random order on the same day. A correction equation was derived based on the adult experiments and tested on the preschool data. Results Increasing the Vd of the N2 MBW system resulted in a higher lung clearance index (LCI). A strong non‐linear relationship between N2 LCI and the Vd/tidal volume was observed. When the Vd was equivalent between systems, LCI measured by the SF6 MBW system was similar to that measured by the N2 MBW. LCI was higher on the N2 MBW than the SF6 MBW in preschool children. Correcting for the equipment Vd of the N2 MBW resulted in better agreement. Conclusions Equipment Vd affects LCI measurements especially in young children where Vd is large relative to lung volumes.